Repackaging agricultural research for greater impact on agricultural growth in Africa - Seck, P.A.; Agboh-Noameshie, A.R.; Diagne, A.; Bamba, I. (Science and Education Publishing Co., Ltd., 2013)
Despite the enormous research activities embarked upon by the various research entities in Africa over time, the expected research impacts remain obscure. This paper is a compilation of facts and figures from published peer reviewed articles, agricultural research and development reports from national and international institutions, and base-line data from the Africa Rice Centre aimed at elucidating the performance of agricultural research in Africa between 1960 and 2010. It discusses the constraints to the visible impact of agricultural research on the growth of Africa’s economy, and suggests how to repackage agricultural research for more visible impact on Africa’s economic growth. Results show that agricultural research has been beneficial for African agriculture widely and is believed to be the backbone of the economic growth of the continent. Agricultural research has also served as the bedrock of agricultural technological transformation to enhance agricultural growth. Research has helped to increase agricultural production and productivity and food security in several countries. Also, investment in agricultural research has yielded positive impact on poverty reduction and food security. However, food security and poverty are still visibly mining the African population. The major constraints in the utilization of agricultural research results are the lack of adequate public investment in agriculture, lack of well-trained researchers, inadequate research infrastructures and poor management of the agricultural research and development system. Findings show that in order to package agricultural research for visible impact on the economy, agricultural research systems would need to be adequately funded and handled by skilled human resources under good governance. An effective innovative agricultural policy would demand the initial acknowledgment that a break from the past is necessary to ‘produce more and better’ in Africa and that successful agricultural research systems should be designed in a framework of co-construction, co-execution and co-evaluation.